A Japanese nationwide survey of 23-valent pneumococcal capsular polysaccharide vaccine (PPSV23) coverage among patients with chronic medical condition aged 50 and older. Issue 7 (2nd July 2020) - Kawakami, Kenji; Nakamura, Atsushi; Wakana, Akira; Folaranmi, Temitope A.; Iino, Tomoharu
ABSTRACT: The 23-valent capsular polysaccharide pneumococcal vaccine (PPSV23) was introduced in Japan's routine immunization schedule October 2014. It was recommended for adults aged 65 years (including those ≥65 during the transition period), and for adults 60–64 with cardiac, renal, or respiratory dysfunction equivalent to Level 1 physical disability. Several studies have shown that patients aged 50+ with chronic medical conditions (CMC) are at elevated risk of pneumococcal infection. Nonetheless, PPSV23 vaccination rates among this population remains low. In our study, we report the results of a survey investigation into PPSV23 vaccination rates among Japanese patients aged 50+ with CMC. Patients aged 50+ comprised the patient population (n = 5, 078) and internal medicine physicians comprised the doctor population (n = 400) located all over Japan were asked an array of questions relevant to PPSV23 immunization in June 2018 via Web-based surveys. PPSV23 coverages among chronic patients aged 50–59, 60–64, and 65+ years were respectively 1.3%, 2.9%, and 37.8%. The high disease-specific PPSV23 rates seen in the 65+ group was 50.0% and 49.4%, for chronic liver disease and chronic lung disease, respectively. Doctors most frequently cited a lack of municipal subsidies as justification for recommending the vaccine to patients with CMC aged 50–64 years, and deference to patients' wishes as justification for patients with CMC aged 65+. In conclusion, PPSV23 has poor coverage among Japanese adults aged 50–64 with CMC. Doctors and local authorities need to raise public awareness to improve the vaccination rate, given the high risk of pneumococcal infectious disease among patients with CMC.